Somatic alterations in circulating cell-free DNA of oesophageal carcinoma patients during primary staging are indicative for post-surgical tumour recurrence. Issue 1 (December 2018) - Pasternack, Helen; Fassunke, Jana; Plum, Patrick; Chon, Seung-Hun; Hescheler, Daniel; Gassa, Asmae; Merkelbach-Bruse, Sabine; Bruns, Christiane; Perner, Sven; Hallek, Michael; Büttner, Reinhard; Bollschweiler, Elfriede; et al.
Abstract Oesophageal cancer (OC) has high mortality. This study aims at determining the feasibility of liquid biopsies for genomic profiling in early stage OC, comparing two different technologies for mutational analysis in circulating cell -free DNA (ccfDNA) and evaluating the clinical impact of these somatic alterations during primary staging. In 25 patients with locally advanced OC, endoscopic tumour biopsies and simultaneous blood samples were taken during primary staging. Genomic DNA from biopsies and ccfDNA were analysed for mutations using a 12 gene panel next-generation sequencing (NGS) assay as well as digital droplet PCR (ddPCR). Genetic data was correlated with patients' outcome. In 21 of the tested biopsies (84%) at least one somatic mutation was detected by NGS. Mutations detected by NGS were detectable by ddPCR with similar allele frequencies. In three out of the 21 patients with proven mutations, the same mutations were also detectable in ccfDNA using NGS (14%). In contrast, ddPCR detected mutations in ccfDNA of five additional patients (8/21, 38%). Post-surgical outcome analysis was performed for those patients who had received complete tumour resection (n = 16). Five of them suffered from an early relapse within the first year after surgery, including four with detectable somatic mutations in ccfDNA during primary staging. Taken together, we showed a higher sensitivity for ddPCR compared to NGS in detecting mutated ccfDNA in OC. Detection of somatically altered ccfDNA during primary staging seems to be indicative for post-surgical tumour recurrence.